The Struggles of Asian Immigrants in the Documentary “Being Asians in America (2022)” - Andika Heka Putra; Sukarni Suryaningsih, M.Hum. (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2026)
Documentary films are one of the media which are able to represent social reality while building public understanding of the experiences of minority groups. This study aims to analyze the representation of the struggles of Asian immigrants in the documentary Being Asians in America (2022) produced by the Pew Research Center. The research uses a descriptive qualitative approach with the film text analysis method. The research data in the form of dialogues, narratives, and scenes related to the experiences of Asian immigrants were then analyzed using the perspective of Critical Race Theory to uncover power relations, discriminatory practices, and representational politics built in the film. The results show that this documentary represents the experience of Asian immigrants as a complex process, from the arrival of Chinese, Japanese, Sikhs, and Pakistanis to the United States to their struggles with stereotypes, discrimination, hate crimes, physical violence, language barriers, and limited access to social and economic opportunities. On the other hand, the film also shows various adaptation strategies carried out by immigrants through education, entrepreneurship, community solidarity, and the preservation of cultural identity as a form of resistance to marginalization.